STABILIZATION OF CLAY AND RESIDUAL SOILS USING CEMENT - RICE HUSK ASH MIXTURES - Agus Setyo Muntohar, Ehammed A.Basha, Roslan Hashim (Jurnal Teknik Sipil UNPAR, 2004)
The well established techniques of soil stabilization often use such cementing agents as Portland cement, lime, etc. Replacement of those cementing materials with industrial or agricultural by-product is highly desirable. Rice husk ash is a very potential paddy crop waste as pozzolanic materials which result in a superior properties when combined with cement or other cementing agents. This paper presents the laboratory study on the stabilized soils with cement and rice husk ash. The experimental study included the evaluation of such properties of the soil as consistency limits, compaction, unconfined compressive strength, and X-Ray diffraction. Three types of soils are used in this study i.e granite residual soils, kaolinite clay and montmorillonite clay (bentonite). Test results show that both cement and rice husk ash reduces the plasticity of soils. In term of compactability, addition of rice husk ash and cement decreases the maximum dry density and increases the optimum moisture content. From the viewpoint of plasticity, compaction and strength characteristics, and economy, addition of 6 – 8 percent cement and 10 – 15 percent rice husk ash are recommended as an optimum amount for soils stabilization.